Social Costs of the European Union in the Context of the Economic-Financial Crisis - Andreea Gradinaru (CES Working Papers, 2013)
The start of the financial crisis in mid-2007 at a global scale had a major impact on the European Union's economy. All member states have been economically affected, but the social effects were mainly of large amplitude. This paper focuses precisely on analysing the social costs which the economic-financial crisis has generated in the European Union. After finishing the study we have noticed that numerous social consequences of the recession have manifested intensely since the beginning of the crisis and continue to do so even today. These consist in the increase of poverty and social exclusion, rise in unemployment, decrease in birth rate, changes regarding the migration process, reduction in income, excessive indebtedness, the disparities between countries contributing to the augmentation of all these.
Keywords: G01; 330; unemployment; poverty; crisis; social gaps; migration; birth rate Romania